‘Borrowed borrowings’ traced from Sanskrit to Malay to Malaysian English / Manjit Kaur Balwant Singh - Manjit Kaur , Balwant Singh (2019)
This research investigates the influence of Sanskrit language in Malaysian English tracing the indirect route of the loanwords through Malay as the intermediary language, known as the phenomenon of “borrowed borrowings” in this study. The Sanskrit loanwords found in the online versions of the Malay Newspapers; Berita Harian and Utusan, were examined for their current change in form and function in the process of acculturation by the multicultural speakers and the same procedure was applied to trace these loanwords in the online versions of the Malaysian English Newspapers; the Star and New Straits Times. The Old Malay language was heavily influenced by Sanskrit around the seventh century. Examples include words like Maharddhika ‘prosperous’ borrowed as Merdeka ‘independence’ in Malay which are also found with the same meaning in Malaysian English. These changes were analyzed using Haugen's (1950) theoretical framework of lexical borrowing and recent developments in the field. The categories of loanwords found in the written data were mostly loanwords, derivational and compound blends, and semantic loans. The Malaysian English has been researched for influences of Malay, Chinese and Tamil, the three major languages in Malaysia, but rarely has the indirect influence of the minority groups speaking Indic languages under the Sanskrit umbrella been investigated in its rich tapestry.